Histidine‐Rich Glycoprotein Alleviates Liver Ischemia/Reperfusion Injury in Mice With Nonalcoholic Steatohepatitis. Issue 6 (8th June 2021) - Guo, Jie; Akahoshi, Tomohiko; Mizuta, Yukie; Murata, Masaharu; Narahara, Sayoko; Kawano, Takahito; Nagao, Yoshihiro; Zhang, Shuo; Tomikawa, Morimasa; Kawanaka, Hirofumi; Hashizume, Makoto
Abstract : Hepatic ischemia/reperfusion injury (IRI) is a major complication of liver surgery and transplantation, especially in patients with nonalcoholic steatohepatitis (NASH). The mechanism of NASH susceptibility to IRI has not been fully clarified. We investigated the role of liver‐produced histidine‐rich glycoprotein (HRG) in NASH IRI. A NASH mouse model was established using C57BL/6J mice fed a methionine‐choline–deficient diet (MCDD) for 6 weeks. The MCDD and standard diet groups were exposed to 60 minutes of partial hepatic ischemia/reperfusion (I/R). We further evaluated the impact of HRG in this context using HRG knockdown (KD) mice. IRI increased HRG expression in the standard diet group, but not in the MCDD group after I/R. HRG expression was inversely correlated with neutrophil infiltration and the formation of neutrophil extracellular traps (NETs). HRG KD mice showed severe liver injury with neutrophil infiltration and the formation of NETs. Pretreatment with supplementary HRG protected against I/R with the inhibition of neutrophil infiltration and the formation of NETs. In vitro, hepatocytes showed that the expression of HRG was upregulated under hypoxia/reoxygenation conditions, but not in response to oleic acid–treated hepatocytes. The decrease in HRG expression in fatty hepatocytes was accompanied by decreased farnesoid X receptor and hypoxia inducible factor 2 alpha subunit expression. HRG is a hepatoprotective factor during hepatic IRI because it decreases neutrophil infiltration and the formation of NETs. The decrease in HRG is a cause of susceptibility to IRI in steatotic livers. Therefore, HRG is a new therapeutic target for minimizing liver damage in patients with NASH.